Integrasi Daya Tarik Wisata Kota Denpasar Bali - I Gusti Bagus Rai Utama (Jurnal Perkotaan, 2017)
The model of the development of an integrated city tourism urgently to be done for the short- term and long-term. Develop urban area is an attempt to increase revenue through taxes hotels, restaurants, and simultaneously increase the economic activity in urban areas. The good management of the city tourism will realize the satisfaction of all parties. Some of the cities in Indonesia deserves to be developed as a city tourism when viewed from multiple components as tourism attractions. These components are like: the town hall, roads that meaningful myth, historical monuments, culinary, college or university, shopping malls, traditional markets, squares, parks, museums, fairs, and other attractions. To be able to make it as a tourist product, the necessary integration related aspects comprising aspects of the attraction of the city, the transportation aspect, the aspect of main and supporting facilities, and institutional aspects such as the attributes of human resources, systems, and other related institutions. The city of Denpasar as as a business center of the activity in case the tourists both domestic and foreign tourists, require restructuring. Structuring urgent to do is structuring the local community business centers, the arrangement of lodges or hotels, and the area attractions management.